Realized Students Well-Being Through Self-Development Programs: Investigate The Role Of Student Guidance Activities Based On Practical Life Skills - Shafira Nurulita Salehuddin; Ahmad Yusuf Sobri; Yudithia Dian Putra (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
This research is important because it discusses the integration of practical life skills as a fundamental component for realizing student well-being. The aim is to investigate in depth the role of these skills-based student development activities. This research adopted a qualitative approach with a single case study design at BA Restu 1, with data collected through interviews, observation, and documentation. Data analysis included data condensation, presentation, and verification. The results show that the student development program realizes child well-being through four aspects practical life skills that form the foundation for independence and self-confidence; social skills development that fosters a sense of belonging; integration of character development that transforms moral values into concrete behavior; and interest-based curriculum that increases children's autonomy and intrinsic motivation. The implication of these findings is holistic student development program is a fundamental component, not merely an addition, in creating a learning environment that supports children's holistic development.